Proactive and visual approach for product maintainability design. (January 2023) - Geng, Jie; Gao, Zhuoying; Li, Ying; He, Zhiyi; Yu, Dequan; Wang, Zili; Lv, Chuan
Abstract: Maintainability design, as a vital element in product design, is generally conducted after the physical or virtual prototype is done, and this design way always accompanies with the characters of lag, passiveness, subjectivity and lack of relevance. And even design flaws are exposed based on corresponding maintainability analysis, the improvements are hardly finished owing to various practical difficulties. This paper proposed a novel proactive maintainability design method. Based on the maintainability and functionability/structurability (F/S) factors of the product first, a "many to many" mapping relationship between maintainability and F/S spaces is established, in which quantitative assessment and visualization representation are two aspects. Separately, the quantitative assessment provides an objective and precise result of relationship confirmation, and the visualization representation brings a comprehensive and intuitive way for maintainability and F/S designers. Finally, the case study section shows the availability and effectiveness of the methodology by verification and comparison. The proposed methodology considers maintainability affection on F/S just from the start point of product design. Hence, compared with the physical prototype and virtual prototype approach, the implementation of the proposed methodology can make maintainability design and functional/structural design to be conducted almost simultaneously.